Islamic Education Perspective of Abdurahman Mas'ud - Sukron, M. (Journal Corner of Education, Linguistics, and Literature, 2024)
This research aims to examine Abdurahman Mas'ud's thoughts regarding Islamic education, which is seen as a process that not only leads to intellectual development, but also liberation and social transformation. This research is descriptive qualitative research with literature study. With primary data sources coming from interviews and secondary sources coming from scientific publications in the form of books, journals, articles and other research results. The results of this research show that in Mas'ud's perspective, Islamic education must integrate worldly knowledge with religious values to form individuals who have a balance between moral, spiritual and intellectual aspects. The concept of inclusive and democratic education is an important part of his thinking, where education must be accessible to all levels of society regardless of social or economic status. Apart from that, according to Mas'ud, Islamic education focuses on building character, independence and ethics that are based on Islamic teachings, and are able to equip individuals to face the challenges of the world and the hereafter. This article also explores the relevance of Abdurahman Mas'ud's thoughts in the context of Islamic education in Indonesia today.